Implementation of PBL-Based Experimental Method Improves Students' Physics Learning Outcomes - Simangunsong, Ika Trisni; Simbolon, Merta; Rezeki, Nani Sri; Damanik, Dede Parsaoran (Lensa: Jurnal Kependidikan Fisika, 2025)
Education plays a role in improving student understanding. Improving learning outcomes is influenced by a supportive learning environment. This class action research aims to see the improvement of students' physics learning outcomes through the application of the experimental method based on Problem Based Learning in the odd semester of the 2024/2025 school year. Students of class XII-6 of one of the high schools in Merauke became the sample of this study, there were 35 students.  The form of research used in classroom action research. Instruments used in teacher validation, to be adjusted to the expected learning outcomes, consisting of 5 essay questions. The indicators of the success of the study are, (1) The criteria for classical completeness of all students ≥ 85%. (2) the minimum criteria of the class is ≥70. The application of the PBL-based experimental method was completed after applying cycle II. The final results found 28 students experienced learning completeness. The achievement of 80% of students who were classically complete, and also reached the minimum criteria. There is an increase in student learning outcomes through the application of PBL-based experimental methods.